Addiction a Complex Syndrome (Journal of Fatima Jinnah Medical University, 2024)
Addiction is a complex and multifaceted issue that affects millions of people worldwide. It has the potential to ruin lives, destroy families, and damage communities. Addiction can be defined as a compulsive and uncontrollable urge to engage in a particular behaviour, despite the negative consequences that may result.1 It can take many forms, from alcohol and drugs to gambling, sex, and even food. Addictive behaviours have a profound impact on individuals and society as a whole.          The origin of addiction is still a topic of debate among scholars and researchers, with some pointing to genetic predispositions and others highlighting environmental factors such as childhood trauma and stress. Whatever the cause, addiction is a chronic condition that requires support, understanding, and intervention to overcome.2          One of the most significant challenges of addiction is that it is often associated with negative stigmas, shame, and guilt. Many people who struggle with addiction do so in silence, afraid to seek help or admit they have a problem. This stigma can make it difficult for individuals to access the resources and support they need to overcome their addiction.3